Information system for sounding Ukrainian-language text based on NLP methods and machine learnin - Byelousov Illya; Vysotska Victoria; Shakleina Iryna (онлайн, 2022)
This work is devoted to developing an information system for sounding Ukrainian-language text based on NLP methods and machine learning. The authors analyzed the pros and cons of the implemented software solutions for the Ukrainian-language text and took them into account during the implementation of the information system. Methods and frameworks that ensure theapplication's correct, fast and stable operation are also described. A user manual has been created for the correct use of the created system. All processes of using the program are shown, and the control example for productivity confirmation and work of the program is analyzed.